Structural behaviour and design of dowel groups Experimental and numerical identification of stress states and failure mechanisms of the surrounding timber matrix. (15th January 2017) - Hochreiner, G.; Bader, T.K.; Schweigler, M.; Eberhardsteiner, J.
Highlights: Post elastic load carrying behaviour of the timber matrix loaded by dowel groups. Identification of the changing structural systems based on subsequent crack formation. Decomposition of complex loading. Support and extension of the present design process by engineered numerical modelling. Abstract: Dowel-type fasteners in combination with steel plates are widely used in engineered timber structures. Since dowel groups are designed as semi-rigid connections subjected to an arbitrary set of internal forces, the corresponding structural behaviour of the surrounding timber matrix must be considered in the design process accordingly, including the effect of reinforcements. Corresponding stress states and failure mechanisms in the timber matrix of dowel groups are discussed herein. Surface strain fields from tests of dowel groups under complex loading situations were used to identify the sequence of cracking, as well as to assign the related failure modes. First cracking events were caused by stress peaks at the most loaded dowels and by a combination of shear stresses and stresses perpendicular to the grain, while later cracking events were associated with a predominant action of individual stress components. Thus, the non-linear global moment-relative rotation behaviour of dowel groups could be related to failure mechanisms in the surrounding timber matrix. The corresponding strain state was qualitatively as well as quantitatively reproduced by means of a numerical model, which gave access to stresses in the timber matrix and has potential to be implemented as a sub-model in engineering design software. The numerical model supported the feasibility of a decomposition of the stress state due to the global bending moment into stresses caused by a couple of equal forces parallel and perpendicular to the grain, which could be used in the design process. Based on experimental and numerical findings, essential aspects for a design procedure for the timber matrix in dowel groups loaded by a combination of internal forces are proposed.